Osteotomy of the radius and ulna for the Madelung deformity - Fernando Baldy dos Reis; Marcos Katchburian; Flávio Faloppa; Walter Manna Albertoni; José Laredo Filho (1998)
The Madelung deformity can result in pain and decreased function of the wrist and hand. None of the surgical techniques available has been shown consistently to improve grip strength, range of movement or relieve pain. In this prospective study we have treated 18 patients with the Madelung deformity (25 wrists) by wedge subtraction osteotomy of the radius and shortening of the ulna. Our results show statistically significant improvement in grip strength and range of movement of the wrist and forearm. Pain improved in 80% of the patients and 88% were satisfied with the appearance. One patient had a wound infection and another developed reflex sympathetic dystrophy. Two had some recurrence due to continued growth of the ulna and it is recommended that the procedure be delayed until skeletal maturity, or else combined with epiphysiodesis of the ulna.